Kepastian Hukum Status Barang Bukti yang Diduga Hasil Tindak Pidana Pencucian Uang dari Tindak Pidana Asal Narkotika terhadap Terdakwa yang Meninggal Dunia - Trapsilo, Lier Budhi; Maryano, Maryano; Ismed, Mohamad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The problematic confiscation of assets of money laundering defendants whose convictions were finalized and subsequently dismissed by the court due to the defendant's death is the focus of this thesis research, which examines the duties of law enforcement agencies—the prosecutor's office and the police—to recover state assets owned by heirs who received assets from money launderers, through mechanisms in accordance with the principle of the presumption of innocence. The research questions are formulated as follows: 1) What are the provisions in the Money Laundering Law related to narcotics crimes? 2) What is the legal certainty regarding the status of evidence suspected of being the proceeds of money laundering from narcotics-based crimes against deceased defendants? The research method used in this dissertation is a normative juridical research method, conducted in an effort to obtain the necessary data related to the problem. The data used are secondary data and tertiary legal materials. In addition, primary data is also used to support the secondary legal materials. Data analysis is carried out using a qualitative juridical analysis method. Using a theoretical framework, namely the theory of evidence and the theory of legal certainty, to examine this problem. The research results indicate that the law does not regulate a mechanism for the restitution of state losses for deceased convicts, as this contradicts Article 83 of the Criminal Code. Consequently, there is no legal certainty regarding the status of evidence suspected of being the proceeds of money laundering from narcotics-based crimes against deceased defendants. Proven state losses that must be returned cannot be carried out by prosecutors acting as executors for deceased convicts. State attorneys can file civil lawsuits against the convict's heirs to repatriate assets obtained from money laundering to the state or state treasury as state revenue. The author's recommendation to legislators is to add articles that clearly relate to the mechanism for executing compensation or procedures for the restitution of state losses in the form of compensation to the provisions of the law, as well as to enable heirs of convicts convicted of money laundering to fulfill their legal responsibility, namely to return assets used by the heirs of convicts convicted of money laundering.